Gaseous nitrogen losses from cropped and summer-fallowed soils - Aulakh, M. S., author; Rennie, D. A., author; Paul, E. A., author; Agricultural Institute of Canada, publisher (Colorado State University. Libraries, 1982)
A study designed to assess gaseous losses of N as N2O and N2 from soils of conventional till fields seeded to wheat in the Chernozemic soil region of Saskatchewan, together with limited supporting laboratory investigations, has confirmed that for the May-November period losses were in the vicinity of 3 kg N∙ha−1 or less. In contrast, total losses from a summer-fallowed field were approximately 300% higher. Comparisons at one site were made of N losses from a conventionally tilled and zero-tilled Dark Brown Chernozemic soil seeded to wheat; the total losses of N were twice as high for the zero till as the conventional till treatments. The N2O fluxes were shown to be the result of both reductive (denitrification) and oxidative (nitrification) processes and generally, under the conditions of these field experiments, both occurred simultaneously. This experiment also confirmed that C2H2 inhibited nitrification in a manner very similar to N-serve, a well-known nitrification inhibitor.
Keywords: oxidative; quantification; reductive; N losses; measurement